Illocutionary Acts in Kenny Sebastian's Stand-Up Comedy YouTube Videos - Risnawati, Ela; Kustanti, Dewi; Budiarti, Dian (LPPM Universitas Bina Sarana Informatika, 2025)
This research identified the use of illocutionary acts in Kenny Sebastian’s stand-up comedy performances on YouTube, focusing on their role in humor and audience engagement. The research employs a qualitative descriptive method by analyzing three performances, identifying 198 illocutionary acts consisting of representatives (67), directives (54), commissives (11), expressives (49), and declarations (17). Data were categorized using Austin and Searle’s (1979) classification. The findings show that representatives, as the most frequent type, function to criticize, reflect, and describe situations humorously. Directives engage the audience by prompting responses, while expressives convey emotions such as amusement, sarcasm, or gratitude. Commissives contribute to comedic exaggeration through promises or refusals, and declarations create dramatic or authoritative comedic effects. These results highlight how illocutionary acts shape comedic narratives and enhance audience interaction. Future research could explore how different comedy styles or cultural contexts affect the use of speech acts in stand-up comedy.